Manual on the measurement of volunteer work. - Office, International Labour (International Labour Office, 2012)
This manual presents a data collection strategy for measuring volunteer work that is cost-effective and reliable. It provides a definition of volunteer work, a measurement methodology to identify volunteer workers and their characteristics, and an estimation methodology to value their work. The 18th ICLS discussed and approved the Manual in 2008, making this the first-ever internationally sanctioned guidance to national statistical agencies for generating official statistics on volunteer work, using a common definition and approach.